SMARTPHONE ANDROID SEBAGAI PERANGKAT BELAJAR PEMROGRAMAN PYTHON BAGI SISWA SMK - Hery Sunandar; Yasir Hasan (LPPM Universitas Bina Bangsa, 2023)
The increasing need for technology continues to grow every year. One area that is growing is computer programming. However, there are still many vocational students who have not had access and the opportunity to learn computer programming. Therefore, this community service aims to introduce the use of an Android smartphone as a Python programming tool for SMK students. The tools used in this project are Pydroid, Google Colab, and Kivy. Pydroid is a Python development application for Android smartphones, Google Colab is a programming platform for developing and executing Python code online, while Kivy is a framework for developing multitouch-based applications on various platforms such as Android, iOS and desktop. It is hoped that this research can be an alternative for vocational students who have limited access to programming tools in general and can enrich programming learning methods at school